Improving Security in Violent Conflict Settings : Security and Justice Thematic Paper - Spear, Joanna; Harborne, Bernard (Washington, DC: World Bank, 2012)
Acknowledges that security--both physical security and national security--needs to be addressed in contexts ranging from pre-conflict, conflict, to post-conflict, and in both national and local units. Solutions to stemming violence do not follow linear or sequential implementation. Capacity building requires security sector reform, peacebuilding, parliamentary oversight, civil society involvement, financial management, and transitional justice measures. The return of counterinsurgencies in rogue states or rebellions of secessionist movements has focused aid donors on the legitimacy of such groups. In countries like Colombia where disarmament, demobilization and reintegration (DDR) programs were left incomplete, gang violence has escalated, and in countries like El Salvador violence has mutated across generations into transnational gangs. DDR, a popular set of activities to fund, has the potential to achieve security objectives and social welfare, but requires confidence in the government, community acceptance, a sufficiently strong economy, integration of ex-combatants into new armed forces or national service corps, and community involvement.